Results and current approach for Brachial Plexus reconstruction - Bertelli, Jayme A; Ghizoni, Marcos F (Journal of Brachial Plexus and Peripheral Nerve Injury, 2011)
We review our experience treating 335 adult patients with supraclavicular brachial plexus injuries over a 7-year period at the University of Southern Santa Catarina, in Brazil. Patients were categorized into 8 groups, according to functional deficits and roots injured: C5-C6, C5-C7, C5-C8 (T1 Hand), C5-T1 (T2 Hand), C8-T1, C7-T1, C6-T1, and total palsy. To restore function, nerve grafts, nerve transfers, and tendon and muscle transfers were employed. Patients with either upper- or lower-type partial injuries experienced considerable functional return. In total palsies, if a root was available for grafting, 90% of patients had elbow flexion restored, whereas this rate dropped to 50% if no roots were grafted and only nerve transfers performed. Pain resolution should be the first priority, and root exploration and grafting helped to decrease or eliminate pain complaints within a short time of surgery.